2016
DOI: 10.1159/000443124
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-Pharmacological Characterization of Cardiomyocytes Derived from Human Induced Pluripotent Stem Cells

Abstract: Background/Aims: Common systems for the quantification of cellular contraction rely on animal-based models, complex experimental setups or indirect approaches. The herein presented CellDrum technology for testing mechanical tension of cellular monolayers and thin tissue constructs has the potential to scale-up mechanical testing towards medium-throughput analyses. Using hiPS-Cardiac Myocytes (hiPS-CMs) it represents a new perspective of drug testing and brings us closer to personalized drug medication. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…Blocking effects on I CaL change the shape of the displacement‐time curve and decrease its amplitude as shown in Figure and Table . This is consistent with other computational and experimental studies where hiPSC‐CMs were used. The APD90 is found to decrease (Table ), which was also found in a recently published computational and experimental study with the Cor.4U cell line .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Blocking effects on I CaL change the shape of the displacement‐time curve and decrease its amplitude as shown in Figure and Table . This is consistent with other computational and experimental studies where hiPSC‐CMs were used. The APD90 is found to decrease (Table ), which was also found in a recently published computational and experimental study with the Cor.4U cell line .…”
Section: Discussionsupporting
confidence: 91%
“…MEA measures the extracellular field potential and based on that the conduction speed (CS) of the action potential throughout the tissue can be derived. The CellDrum was developed in our institute and is used for mechanical measurements. It is a circular well (radius r = 3.2 mm) in which the tissue construct (silicone membrane and cell monolayer) is clamped.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a previous study has demonstrated that iPSCs possess the characteristics of embryonic stem cells [24], and embryonic stem cells have also been demonstrated to have an unlimited proliferative potential as well as the ability to differentiate into almost any type of tissue [25]. Because of this, iPSCs have a stronger ability to proliferate than differentiated cells and were predicted to be transferred into adult cells via parallel mathematical modeling and numerical simulation [26]. Studies have shown that in successfully induced stem cells with a differentiation potential, a number of embryonic stem cell protein markers such as NANOG, SSEA-3, SSEA-4, TRA-1-60 and TRA-1-81 are expressed [27-29], wherein SSEA-3 and SSEA-4 are cell membrane proteins, TRA-1-60 and TRA-1-81 are cytoplasmic proteins, and NANOG is a cell nuclear protein [30-32].…”
Section: Discussionmentioning
confidence: 99%
“…For thin cardiac tissue constructs these tasks have been addressed with a device called CellDrum [24,25]. The CellDrum is a circular, 4 μm thin silicone membrane with a diameter of 16 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, parameters for passive and coupling models can be determined [26]. Drugs have already been applied to the culture medium leading to phenomenologically observable changes in the beating frequency, deflection, contraction duration, activation time, relaxation time and resting time [25]. Frotscher et al [14,26,27] developed an electromechanical model of the CellDrum which they parametrized, verified and validated using respective experiments.…”
Section: Introductionmentioning
confidence: 99%